Sleep Disturbances and Depression Are Co-morbid Conditions: Insights From Animal Models, Especially Non-human Primate Model - Li, Meng; Cui, Jieqiong; Xu, Bonan; Wei, Yuanyuan; Fu, Chenyang; Lv, Xiaoman; Xiong, Lei; Qin, Dongdong (Frontiers in Psychiatry, 2022)
The incidence rates of depression are increasing year by year. As one of the main clinical manifestations of depression, sleep disorder is often the first complication. This complication may increase the severity of depression and lead to poor prognosis in patients. In the past decades, many methods have been used to evaluate sleep problems, such as polysomnography and electroencephalogram, actigraphy and videography. A large number of rodent and non-human primate models have reproduced the symptoms of depression, which also show sleep disorders. The purpose of this review is to examine and discuss the relationship between sleep disorders and depression. To this end, we evaluated the prevalence, clinical features, phenotypic analysis, and pathophysiological brain mechanisms of depression-related sleep disturbances. We also emphasized the current situation, significance, and insights from animal models of depression, which would provide a better understanding of the pathophysiological mechanisms between sleep disturbance and depression.